Quran and Hadith Learning at SD 23 at Sabang City - Mahliati (International Journal Education and Computer Studies (IJECS), 2023)
This research delves into the dynamics of Quran and Hadith education at SD 23 Kota Sabang, a public school in the city. With a participant pool of 30 students, this study aims to understand and improve the methods employed in teaching these sacred texts. The primary objective is to instill fundamental skills such as reading, writing, and a profound appreciation for the Quran and Hadith, aligning with the broader goal of nurturing ethical behavior guided by these teachings. The research unfolds over two months, involving daily 15-minute sessions. The initial phase emphasizes foundational strategies, predominantly utilizing lecture-style teaching. Challenges encountered include limited resources, time constraints, and students lacking basic Quranic reading skills. The subsequent phase introduces adjustments, such as grouping students based on proficiency and integrating supplementary activities to sustain interest. Key findings highlight the prevalence of lecture-based teaching methods, indicating the need for diversification. Challenges include insufficient resources, time constraints, and students' initial reading skills, demanding tailored solutions. Recommendations involve increased parental involvement, collaborative sharing of effective teaching methods among educators, and enhanced support from school administrations